2005
DOI: 10.1097/00005650-200502000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coding of Heart Failure and Comorbidities in Administrative and Clinical Data for Use in Outcomes Research

Abstract: The ICD-9 428 primary diagnosis is highly predictive of heart failure using clinical criteria. Examination of hospitalization data up to 1 year prior to the index admission improves comorbidity detection and may provide enhancements to future studies of heart failure mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
219
2
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 316 publications
(236 citation statements)
references
References 25 publications
10
219
2
3
Order By: Relevance
“…127 CIHI diagnostic codes in general have demonstrated high agreement for both primary (81-95%) and secondary (88-99%) diagnoses. 128 The OHIP physician billings claims and associated diagnostic code for CKD were compared to the medical record and demonstrated a sensitivity of 74%, specificity of 99%, positive predictive value of 29%, and negative predictive value of 99%.…”
Section: Chronic Kidney Diseasementioning
confidence: 96%
“…127 CIHI diagnostic codes in general have demonstrated high agreement for both primary (81-95%) and secondary (88-99%) diagnoses. 128 The OHIP physician billings claims and associated diagnostic code for CKD were compared to the medical record and demonstrated a sensitivity of 74%, specificity of 99%, positive predictive value of 29%, and negative predictive value of 99%.…”
Section: Chronic Kidney Diseasementioning
confidence: 96%
“…Seven studies accepted HF diagnosis documented in the chart (12,(16)(17)(18)(19)(20)(21) and four studies used documented HF diagnosis or a combination of clinical judgement based on information in the chart (eg, test results, diagnostics) (22)(23)(24)(25). Eight studies (15,(25)(26)(27)(28)(29)(30)(31) ascertained HF presence based on diagnostic criteria used by scoring systems from Framingham, Carlson, Boston, the National Health and Nutrition Examination Survey (NHANES), the New York Heart Association (NYHA) or the European Society of Cardiology (ESC). Four studies (25)(26)(27)32) further classified HF according to levels of evidence such as definite or possible HF using the ESC or Boston criteria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Four studies (25)(26)(27)32) further classified HF according to levels of evidence such as definite or possible HF using the ESC or Boston criteria. Two studies compared the PPV against different clinical definitions of HF, and found that the PPV varied between criteria used (Lee et al [30], 94% Framingham versus 89% Carlson; McCullough et al [31], 56% NHANES versus 64% Framingham versus 83% NYHA).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This definition of HF hospitalization was shown to have a positive predictive value of 94% when compared to the Framingham criteria of HF. 16 Death from all causes is the most uncontroversial end point for a clinical trial to assess the achievement for therapeutic intervention in patients with HF. In subjects with previous HF, we also assessed deaths as a secondary outcome.…”
Section: Study End Pointsmentioning
confidence: 99%